SEMANTIC AND LINGUOCULTURAL ANALYSIS OF PROVERBS WITH THE CONCEPT ’FACE’ IN ENGLISH AND UZBEK LANGUAGES - Kholboyeva Iroda Shukhrat Kizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract. Proverbs reflect the worldview, traditions, and cultural values of a nation. The concept of "face" is one of the key cultural and linguistic markers in many societies, including English and Uzbek. This article explores the semantic and linguocultural aspects of proverbs containing the word "face" in both languages, analyzing similarities and differences in their meanings, usage, and underlying cultural implications.